Redesain Panti Rehabilitasi Gangguan Jiwa Yayasan Fajar Berseri dengan Pendekatan Konsep Ekologi Kabupaten Bekasi - Retno Fitri Astuti; Harry Miarsono; Samsul Idris (Prosiding Sains dan Teknologi, 2022)
Human health includes conditions for the fulfillment of body and soul as well as physical health and spiritual health, without healthy conditions humans cannot carry out activities as they should, but amid the increasing needs of life today, humans have many problems caused by economic pressure, experiencing pressure, problems in the family. Currently in Indonesia regarding the number of people experiencing mental disorders, 17% of the 250 million Indonesian population, including patients at the Al-Fajar Seri Foundation, which continues to increase, new patients compared to patients who recovered from the mental disorder rehabilitation center. The Al-Fajar Seri Foundation also has problems. , including the irregular circulation of the rehabilitation center space, small drainage that has the potential to flood during the rainy season, the lack of inpatient buildings that have begun to be damaged and seem inhumane, no facilities to support the healing process, irregular parking areas. Restructuring and redesigning the area and building of the al-fajar serial mental disorder rehabilitation center which aims to build inpatient housing that can accommodate new patients and build humanistic supporting facilities. With an ecological concept approach that focuses on biological architecture that pays attention to the health of residents in terms of psychological factors and alternative architecture so as to produce a green area, in the rehabilitation center area there are vegetable and fruit gardens that function as food for consumption by patients, fish ponds that function as food and used for cultivation, cattle pens, craft workshops that function as productive activities that produce, fields and building forms that correlate the shape of the bow ruler and the traditional dog tagog house which are transformed into an alternative building. Keywords: Redesign, Rehabilitation Center, Problems, Ecological Concept Approach